Immune evasion by Cryptococcus gattii in vaccinated mice coinfected with C. neoformans - Hester, Maureen M.; Carlson, Diana; Lodge, Jennifer K.; Levitz, Stuart M.; Specht, Charles A. (Frontiers in Immunology, 2024)
Cryptococcus neoformans and C. gattii, the etiologic agents of cryptococcosis, cause over 100,000 deaths worldwide every year, yet no cryptococcal vaccine has progressed to clinical trials. In preclinical studies, mice vaccinated with an attenuated strain of C. neoformans deleted of three cryptococcal chitin deacetylases (Cn-cda1Δ2Δ3Δ) were protected against a lethal challenge with C. neoformans strain KN99. While Cn-cda1Δ2Δ3Δ extended the survival of mice infected with C. gattii strain R265 compared to unvaccinated groups, we were unable to demonstrate fungal clearance as robust as that seen following KN99 challenge. In stark contrast to vaccinated mice challenged with KN99, we also found that R265-challenged mice failed to induce the production of protectionassociated cytokines and chemokines in the lungs. To investigate deficiencies in the vaccine response to R265 infection, we developed a KN99-R265 coinfection model. In unvaccinated mice, the strains behaved in a manner which mirrored single infections, wherein only KN99 disseminated to the brain and spleen. We expanded the coinfection model to Cn-cda1Δ2Δ3Δ-vaccinated mice. Fungal burden, cytokine production, and immune cell infiltration in the lungs of vaccinated, coinfected mice were indicative of immune evasion by C. gattii R265 as the presence of R265 neither compromised the immunophenotype established in response to KN99 nor inhibited clearance of KN99. Collectively, these data indicate that R265 does not dampen a protective vaccine response, but rather suggest that R265 remains largely undetected by the immune system.